Quantum Threats To Bitcoin, Cryptocurrency and Blockchain - Rubayat Khan; Mazharul Karim; PhD; Don Roosan; PharmD (Blockchain in Healthcare Today, 2026)
Objective: The authors evaluated how quantum computing threatens the cryptographic primitives used in Bitcoin and other blockchain systems. These findings were translated into a standards-aligned post-quantum migration profile for healthcare ledgers, including consent, identity, provenance, audit, and encrypted off-chain data exchange. Methodology: Narrative analysis, theoretical security analysis, and healthcare-oriented deployment mapping of classical public-key and hash primitives used in blockchain protocols were paired with an implementation-oriented migration profile based on finalized National Institute of Standards and Technology (NIST) post-quantum standards. We summarize the mathematical assumptions underlying Rivest–Shamir–Adleman (RSA), Elliptic Curve Cryptography/Elliptic Curve Digital Signature Algorithm (ECC)/ECDSA, and Secure Hash Algorithm (SHA-2/SHA-3-family) hash functions; analyze their susceptibility to Shor’s and Grover’s quantum algorithms; compare Federal Information Processing Standards (FIPS) 203 Module-Lattice-Based Key-Encapsulation Mechanism Standard (ML-KEM), FIPS 204 Module-Lattice-Based Digital Signature Standard (ML-DSA), and FIPS 205 Stateless Hash-Based Digital Signature Standard (SLH-DSA); and map their distinct roles to healthcare-ledger authorization, auditability, identity, and encrypted off-chain exchange. The term Advanced Hybrid Module-LWE & Code-Based (AHMC) is used only as shorthand for a standards-aligned hybrid PQC migration profile and does not denote a proprietary product, a novel algorithm, or a new cryptographic primitive. Proposed adoption of hybrid, quantum-resistant cryptographic primitives for cryptocurrency wallets, transaction signatures, and ledger security during an interim migration period (hybrid classical + PQC, followed by PQC-only). Qualitative and implementation-oriented assessment of (1) break feasibility of RSA/ECC under Shor’s algorithm, (2) effective security reduction for hash functions under Grover’s algorithm, (3) security assumptions and composition requirements of a standards-aligned hybrid migration profile, (4) transaction-size and verification-cost impact, and (5) healthcare-specific implications for long-retention consent, identity, provenance, and audit records. Results: Shor’s algorithm reduces integer factorization and discrete logarithms to polynomial time, directly compromising RSA and ECC/ECDSA once fault-tolerant, large-scale quantum computers exist. Grover’s algorithm yields a quadratic speedup for brute-force search, effectively halving the security margin of symmetric keys and hash functions at fixed output sizes. The AHMC-L1/L3/L5 profiles use ML-KEM-512/768/1024 for key establishment and ML-DSA-44/65/87 for transaction authentication, with SLH-DSA as a hash-based fallback. During a hybrid ECDSA+PQC migration, verification requires one classical and one PQC verification per authorization; transaction-size overhead is dominated by PQC signatures, approximately 2.4 KB for ML-DSA-44, 3.3 KB for ML-DSA-65, and 4.6 KB for ML-DSA-87 before script and encoding overhead. For healthcare ledgers, these findings support selective use of post-quantum signatures for: high-value state transitions, one-time public-key registration where possible, and continued off-chain storage of protected health information. Deployment suitability remains contingent on workflow-specific latency, storage, availability, key lifecycle, and side-channel testing. Conclusions: Quantum risk to blockchain signatures has direct implications for healthcare systems that depend on long-lived consent, identity, provenance, and audit records. A staged, standards-aligned migration profile can preserve authorization and ledger verifiability while keeping protected health information off-chain. The AHMC label refers only to this migration profile, not to a new cryptographic primitive; healthcare adoption requires open implementations, empirical benchmarking, crypto-agile key governance, and side-channel-resistant engineering.